TALPID3/KIAA0586 Regulates Multiple Aspects of Neuromuscular Patterning During Gastrointestinal Development in Animal Models and Human - Delalande, Jean Marie; Nagy, Nandor; McCann, Conor J.; Natarajan, Dipa; Cooper, Julie E.; Carreno, Gabriela; Dora, David; Campbell, Alison; Laurent, Nicole; Kemos, Polychronis; Thomas, Sophie; Alby, Caroline; et al. (Frontiers in Molecular Neuroscience, 2021)
TALPID3/KIAA0586 is an evolutionary conserved protein, which plays an essential role in protein trafficking. Its role during gastrointestinal (GI) and enteric nervous system (ENS) development has not been studied previously. Here, we analysed chicken, mouse and human embryonic GI tissues with TALPID3 mutations. The GI tract of TALPID3 chicken embryos was shortened and malformed. Histologically, the gut smooth muscle was mispatterned and enteric neural crest cells were scattered throughout the gut wall. Analysis of the Hedgehog pathway and gut extracellular matrix provided causative reasons for these defects. Interestingly, chicken intra-species grafting experiments and a conditional knockout mouse model showed that ENS formation did not require TALPID3, but was dependent on correct environmental cues. Surprisingly, the lack of TALPID3 in enteric neural crest cells (ENCC) affected smooth muscle and epithelial development in a non cell-autonomous manner. Analysis of human gut fetal tissues with a KIAA0586 mutation showed strikingly similar findings compared to the animal models demonstrating conservation of TALPID3 and its necessary role in human GI tract development and patterning